Charge transport in a system of cholesterol molecules deposited on graphene oxide using current sensing atomic force microscope. (2019) - Sarkar, Arup; Suresh, K.A.; Gayathri, H.N.
Abstract: We have made a system consisting of cholesterol (Ch) molecules transferred onto graphene oxide (GO) by Langmuir-Blodgett technique on highly ordered pyrolytic graphite substrate. We have used current sensing atomic force microscope to study the current (I) - voltage (V) characteristics of Ch-GO system. To prepare Langmuir film of GO we have tuned its amphiphilicity by adjusting pH of the subphase. We find quantum tunneling to be the main mechanism of charge transport and it changes from direct to injection tunneling with increase in the applied bias voltage. Our finding can be useful for fabrication of molecular electronic devices.